Central Retinal Artery Occlusion as a Complication in Invasive Aesthetic Cosmetology: a Clinical Case - V. N. Trubilin; E. G. Poluninа; V. V. Kurenkov; K. V. Chinenova; A. S. Yatsun; Yu. V. Evstigneeva (Oftalʹmologiâ, 2021)
Central retinal artery occlusion (CRAO) is a relatively rare form of acute retinal arterial ischemia that results in unilateral vision loss. The incidence of transient vision loss is estimated at approximately 14 cases per 100,000 people per year, while the incidence of CRAO is approximately 1–2 cases per 100,000 people. In the foreign literature, there are more and more publications about the development of iatrogenic vision loss after dermal cosmetic injections. We would like to present a clinical case that should be interesting for both practicing ophthalmologists and specialists of related specialties, especially for cosmetologists. Patient M., 42 years old, came to us with complaints of a sharp loss of vision to light perception in the right eye. From the anamnesis, it is known that two hours earlier, the patient was injected into the temporal region (plasma, anesthetic, epinephrine) in the cosmetology office. Lightning-fast deterioration of vision occurred at the time of the drug administration. The patient arrived at the clinic 2 hours after the onset of complaints. We conducted an ophthalmological examination of the patient, the diagnosis was made: occlusion of the central artery of the retina of the right eye, and immediately performed standard emergency therapy. After a course of conservative treatment in an ophthalmological hospital, a persistent decrease in visual functions and a violation of arterial blood circulation in the central retinal artery basin remained. The progressive increase in the number of minimally invasive cosmetic procedures in recent years, in particular, injections of dermal fillers, is associated with rare, but often fatal complications. This clinical situation should attract the attention of practicing ophthalmologists and cosmetologists to these types of complications, and improve the quality and speed of emergency medical care.